This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 4q )/2  [1/(2p)]/2 U = 4/2 +(7z 4q )/2  (1/4)(1/p) U/ p = (1/4) p 1 p (note: in this partial derivative, treat "z" and "q" as constants) U/ p = (1/4) ( 29 1 p p U/ p = (1/4) (1)p2 6) Find U/ x, given U = 5x 1/2 y 1/3 . U/ x = (1/2)5x1/2 y 1/3 (treating "y" as a constant) 7) Find U/ y, given U = 2x + 3y + xy. U/ y = 0 + 3 + x (treating "x" as a constant) 8) Find U/ y, given U = (1+x)(1+y) (hint: remember the product rule of differentiation) U/ y = 0*(1+y) + (1+x)*(1) (note: in this partial derivative, treat "x" as a constant) U/ y = (1+x) 1...
View
Full
Document
This note was uploaded on 10/22/2009 for the course ECN 321 taught by Professor Dumas during the Fall '08 term at University of North Carolina Wilmington.
 Fall '08
 Dumas
 Economics, Microeconomics

Click to edit the document details